ANALISIS KERUSAKAN AKIBAT MISFIRING PADA MOTOR TORAK DENGAN MENGGUNAKAN METODA GETARAN - Subekti, Subekti; Hidayat, Muhammad Nurul; Effendi, Basuki Dwi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The working principle of the piston engine consists of a system that follows a thermodynamic cycle and a mechanical cycle. The thermodynamic cycle is known as a (P-T) diagram while the mechanical cycle is known as a (P-V) diagram. In operation, the piston engine can move in a rotating manner with a certain rotation because it gets a force that comes from the combustion process. The primary vibration force is caused by the combustion gas pressure in the combustion chamber, such as detonation caused by uneven spraying in the combustion chamber and misfire is characterized by a low maximum pressure using vibration analysis. The higher the amplitude produced by the spark plug, the higher the effect of engine vibration produced. The engine speed, power and load applied to the engine greatly affect the misfiring of the spark plug. Misfiring has a frequency amplitude that tends to be more, this causes the driver discomfort while driving. The frequency that has the highest amplitude is around 100 Hz on misfiring spark plugs, and 120 Hz – 130 Hz on normal spark plugs. At idle engine speed of 900 rpm, 1500 rpm, 2000 rpm, normal spark plugs have the highest amplitude on the X and Y axis channels, while for misfiring spark plugs the highest amplitude is only on the Z axis.